2022
DOI: 10.1155/2022/4708527
|View full text |Cite
|
Sign up to set email alerts
|

Nature against Diabetic Retinopathy: A Review on Antiangiogenic, Antioxidant, and Anti-Inflammatory Phytochemicals

Abstract: Background and Purpose. Diabetes mellitus (DM), hyperglycemia, and hypertension can result in diabetic retinopathy (DR), which is a major cause of blindness on a global scale. Development of DR is associated with decreased endothelial cells, increased basal membrane thickness, permeation of the retinal blood barrier, and neovascularization in patients. The purpose of the present review is to provide an overview of the findings regarding applications of phytochemicals for DR treatment and could be a beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 112 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…Excess ROS production due to hyperglycemia initiates oxidative stress and inflammatory responses, which are mechanisms involved in the pathogenesis of DR [3,7]. Antioxidants with antiinflammatory effects exert inhibitory effects on the onset and progression of DR [41][42][43]. β-asarone, a type of volatile oil, exerts multiple pharmacological effects, including antioxidant and anti-inflammatory effects [19,20,44].…”
Section: Discussionmentioning
confidence: 99%
“…Excess ROS production due to hyperglycemia initiates oxidative stress and inflammatory responses, which are mechanisms involved in the pathogenesis of DR [3,7]. Antioxidants with antiinflammatory effects exert inhibitory effects on the onset and progression of DR [41][42][43]. β-asarone, a type of volatile oil, exerts multiple pharmacological effects, including antioxidant and anti-inflammatory effects [19,20,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression levels of various inflammatory mediators such as tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1), and intercellular cell adhesion molecule-1 (ICAM-1) are increased under the stimulation of persistent hyperglycemia, which has been demonstrated in the vitreous cavity and serum of diabetic patients and various types of diabetic animal models. The anomalies of the aforementioned indicators usually do not appear alone because they influence each other on the basis of their own development; for example, TNF-α aggravates leukocyte adhesion and BRB breakdown, and ICAM-1 is closely related to leukocyte adhesion ( Li W. C. et al, 2020 ; Khazeei Tabari et al, 2022 ; Kovoor et al, 2022 ). It has been reported that many TCMs exhibit against retinal inflammation in diabetes ( Figure 2 ), and the signaling pathways involved are explained in the following paragraphs.…”
Section: Signaling Pathways In Tcm Intervening With Inflammation Of Drmentioning
confidence: 99%